Chemistry and biology of heparin and heparan sulfate - Garg, Hari G., 1931-; Linhardt, Robert J.; Hales, Charles A., 1941- (Elsevier, 2005)
The chemistry, biochemistry and pharmacology of heparin and heparan sulfate have been and continue to be a major scientific undertaking - heparin and its derivative remain important drugs in clinical practice. Chemistry and Biology of Heparin and Heparan Sulfate provides readers with an insight into the chemistry, biology and clinical applications of heparin and heparan sulfate and examines their function in various physiological and pathological conditions. Providing a wealth of useful information, no other tome covers the diversity of topics in the field. Students, doctors, chemists, biochemists, and research scientists will find this book an invaluable source for updating their current knowledge of developments in this area. * Comprehensively reviews all aspects of heparin and heparan sulfate research * Uniquely describes the chemistry, biology and clinical application of heparins and heparan sulfates in one work * Provides an invaluable source of knowledge of current developments for chemists, biochemists, medical doctors, researchers, students and practitioners.